VS38: a new monoclonal antibody for detecting plasma cell differentiation in routine sections. Issue 5 (May 1994) - Turley, H; Jones, M; Erber, W; Mayne, K; de Waele, M; Gatter, K
Abstract : AIMS–To characterise a new mouse monoclonal antibody, VS38, which recognises an intracytoplasmic antigen of 64 kilodaltons present in normal and neoplastic plasma cells; and to establish its value as a diagnostic reagent for routine pathological practice. METHODS–A range of normal and neoplastic tissue sections, both frozen and routinely fixed, were immunostained, using the microwave method of antigen retrieval for routinely fixed specimens. The antibody was also tested on blood and bone marrow specimens and a range of human cell lines. The molecular weight of the antigen recognised by the antibody was obtained by western blot analysis. FACS analysis was used to demonstrate the cellular location of the antigen and its presence on tonsil cell suspensions and myeloma cases. RESULTS–VS38 recognised normal and neoplastic plasma cells in all of the tissues, including all routinely fixed plasma cell neoplasms tested. The antibody also weakly stained epithelial elements within the tissue but was absent from haemopoietic cells of other lineages. CONCLUSION–Antibody VS38 is of potential value in identifying myeloma or plasmacytoma in bone marrow or other tissues. It differentiates lymphoplasmacytoid lymphoma from lymphocytic and follicular lymphoma. It also subdivides large cell lymphomas into two groups which may be a more reliable method of separating these tumours than morphology alone.